Tobacco streak virus: unravelling its significance in sunflower production - Chaitra, G V; Parameswari, B; Anbazhagan, P; Bajaru, Bhaskar; Sakthivel, K; Chalam, V Celia; Anitha, K (Indian Journal of Plant Protection, 2025)
Sunflower Necrosis Disease (SND) is a significant hazard to sunflower farming in the Indian subcontinent, attributed to the Tobacco streak virus (TSV) within the Ilarvirus genus, known for its wider host range. Since its discovery in India in 1997, the disease has evolved into an epidemic, affecting sunflower-growing regions across the country. TSV being a pollen-borne virus exhibits a rapid spread in the field, highlighting the challenge of effective disease management. The virus’s resilience and longevity in sunflower crops are made possible by its broad host range. TSV can attack cotton, sun hemp, mungbean, and groundnut apart from sunflower, showing the virus’s versatility and potential impacts on various agricultural environments. It is essential to comprehend the complex mechanisms behind TSV infection in sunflowers to create effective and focused control measures. This review paper on the impact of TSV in sunflower production aims to explore these areas, elucidating the nature of the virus, its mode of spread, and methods for reducing the hazards involved in sunflower farming.